Polsko-bułgarska i bułgarsko-polska komunikacja kulturowa w kontekście zmian ustrojowych i globalizacji. Obecna, nieznana, nieodkryta - Galia Symeonowa-Konach (Postscriptum Polonistyczne)
This study presents various perspectives on cultural communication issues, in the context of globalization and political and economic transformation in Poland and Bulgaria since the democratic revolution of the 1989. Poland and Bulgaria have old historical and cultural relations, defined and developed institutionally in different spheres of social life at the beginning of the twentieth century. Cultural cooperation is a kind of catalyst for the country’s foreign policy: maintains the historical, ethnic, and regional cooperation, symbolizes the successes, compensates for the negative relations and is an indirect tool for deepening the breakthrough in bilateral relations. Nowadays, branding models are used to promote the image of countries as a tool of the public diplomacy. This article examines the dynamic role of the changes in the crosscultural communication. The article draws on the most important cultural and scientific publications and literature to argue that building this cultural cooperation has its roots in the capability to mobilize and use culture as a resource for collaborative action between Poland and Bulgaria.